Analisis Faktor-Faktor Yang Menentukan Kepatuhan Wajib Pajak UMKM - Datte Salu Tondok; Ignasius Narew; Daniel Nemba Dambe; Tuti Fitriani; Yahya Nusa (Jurnal Ecogen, 2023)
Public awareness as a compliant taxpayer is closely related to public perceptions of taxes that will affect taxpayer motivation to pay taxes. This study aims to determine the factors that influence the compliance of small and medium enterprises (SMEs) taxpayers in Timika City so that it can be taken into consideration for the government or tax authorities in improving community tax compliance, especially MSME actors. The data collected in this study are quantitative data from non-taxpayer respondents who are SME taxpayers.  The sample of this study came from MSME actors in Timika City as many as 100 respondents. Data analysis in this study used confirmatory factor analysis. From the analysis conducted, it was found that knowledge, tax system effectiveness, and income are determinants of tax compliance among SME taxpayers in Timika city.